Promising discovery of three plants with anticancer activity (2020)
Osteosarcoma is the most common type of bone cancer that affects children, adolescents and young adults. It is a disease characterized by having an aggressive treatment and in general a poor prognosis. Its treatment includes radiotherapy, chemotherapy and surgery, that although they seek to improve the overall health of the patient, can cause undesirable side effects in patients, and they do not reach 100% effectiveness. Therefore, it is necessary to search for new effective therapeutic alternatives that do not generate adverse effects and do not involve high medical expenses. Natural medicine is a tool that favors the treatment of different types of cancer, since numerous studies show that plants have components that interfere in the survival and death of cancer cells. For this reason, the objective of this research was to determine the anticancer activity of three plants extracts found in the colombian Atlantic Coast, on two cell lines OSCA-8...